History and its links across the curriculum. Issue 6 (19th September 2018) - Percival, James
ABSTRACT: The Independent Cambridge Review of the Primary Curriculum [Alexander, R., M. Armstrong, J. Flutter, L. Hargreaves, D. Harrison, W. Harlen, and D. Utting. 2010. Children, Their World, Their Education . London: Routledge] advocated 'Eight Domains' through which to organise the primary curriculum, with 'Place and Time' encompassing history. The place of history is thought to be crucial in this process because it acts well as a hub for cross-curricular links. Three models, based on recent research, are presented in this paper. The first argues for history as a lead subject through which other subjects can be linked easily, thus replicating the natural links between the primary subject disciplines and providing economies of time and coverage. Two other thematic approaches are discussed in which learning in history can take a key role in the organisation of the curriculum. The research presented indicates that cross-curricular and thematic forms of curriculum management need not traduce the key disciplinary concepts and skills linked to history.